Sex addiction a guide for couples and those who help them - Hall, Paula (Milton Park, Abingdon, Oxon New York,NY Routledge, 2019)
Sex Addiction: A Guide for Couples and Those Who Help Them is a practical book that provides empathic support, guidance, information and pragmatic strategies for couples who want to survive sex and porn addiction - whether that's together, or apart. Sex and porn addiction devastates couple relationships, and unlike the impact of infidelity, there is no `before' to get back to and no `after'. This book adopts the metaphor of a boat, presenting addiction as the tidal wave that devastates the relation-ship, leaving both crew members fighting for survival. There's guidance to ensure each partner makes it safely back to shore and advice on surveying the damage to your relation-ship and deciding if you want to save it and set sail again. You'll find practical advice for both the partner and the addicted partner, including first-hand accounts of couples that have already undertaken the journey. There are exercises to do alone, and many to share together, to help you understand what's happened, consider your future, and if you choose to stay together, begin the task of rebuilding trust and intimacy. Sex Addiction is not only a practical guide for couples, but also for the therapists who support them. This book will be a companion to Paula Hall's previous books on sex addiction and builds on the already known frameworks and models used, but it is also written to stand alone.
Part I: Surviving the Storm 1. Why sex and porn addiction hurts so much 2. Understanding the reality of sex addiction 3. Prioritising individual recovery 4. Surviving the impact stage Part II: Assessing the Damage 5. Understanding the importance of disclosure 6. Analysing the condition of your relationship 7. Navigating the meaning stage 8. Considering the decision to stay or leave Part III: Re-launching your life - Alone 9. Having a `healthy' divorce 10. Helping children cope with your divorce Part IV: Re-launching your life - Together 11. Acknowledging and accepting new roles 12. Understanding the essential role of forgiveness 13. Rebuilding trust 14. Developing and deepening intimacy.
Includes bibliographical references (pages 209-211) and index.
Keywords: Sex addiction; Sex addiction -- Treatment; Sex addicts -- Family relationships